El Medio Ambiente Y Su Influencia En La Literatura De Mahmoud Darwich Y Juan Ramón Jiménez: Estudio Comparativo - Ahmad Husein Al-Afif (European Scientific Journal, ESJ, 2016)
This article is an attempt to make a comparative literary study on the impact of the environment on the poetry of Mahmoud Darwish and Juan Ramon Jimenez. Both of the famous authors treat the issue of the nature, place, time and environment in a wonderful way that gives us the opportunity to study them as special cases even that both poets didn't live in the same period, but in different times. We have chosen some fragments from their poetry as examples of both poets and we found as a conclusion that the two poets have many things in common, especially they way that they deal with the environment and nature.